Role of inflammatory markers in predicting hepatocellular carcinoma recurrence after liver transplantation - Nourhan Badwei; Waheed A. Monsef; Iman Montasser; Mohamed Bahaa; Mahmoud El Meteini; Shimaa Y. Kamel (Egyptian Liver Journal, 2021)
Abstract Background Liver transplantation (LT) is the best treatment for selected patients with cirrhosis and small hepatocellular carcinoma (HCC) who are not candidates for resection. The proinflammatory effects of systemic inflammatory response have been linked with HCC. Therefore, the measurement of inflammatory markers represents a significant tool to limit recurrence after LT. Results There are eleven patients with HCC recurrence post-transplantation. Pre-transplantation AFP can predict HCC recurrence with the best cutoff value of > 17.8 ng/ml with a sensitivity of 82% and specificity of 70%. Post-transplantation CRP can predict HCC recurrence with the best cutoff value of > 0.85 (mg/dl) with a sensitivity of 73% and specificity of 71%. Other inflammatory markers NLR and PLR were not significant in predicting HCC recurrence. Moreover, HCC recurrence significantly affects the outcome of patients undergoing LT (p value < 0.001) with a worse prognosis. Conclusion Our results showed additional benefits of inflammatory markers as CRP to standard parameters in predicting HCC recurrence to refine recipient selection and achieve better survival outcomes post-LT.